Governance in Crises: Ideologies, Political Systems, and Pandemic Responsiveness - Tang, Phoebe Mengxiao; Patterson, Maxwell (Journal of Leadership, Accountability and Ethics, 2023)
Why are some governments more active in responding to the COVID-19 pandemic than others? Based on ample literature on the political determinants of pandemic responses, this paper seeks to understand the question with an interactive framework of ideology strategies and their political conditions. Resorting to a dataset of 155 countries and their COVID responses in the year of 2020 (before the world enters into the vaccination phase in 2021), we find that government COVID responsiveness is associated with the interactions between the specific character of ideological legitimation strategy (socialist or conservative) invoked by the government and the political system (democratic or decentralized) where it operates. Overall, this research contributes to a multifactor understanding of the political explanations for government responses to crises. It also provides insight for policy choices and designs that are more suitable for the leadership and political contexts.